THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF SOCIO-POLITICAL ANALYSIS OF DIGITAL PROTEST ACTIVITY - M. A. Tanina (Вестник университета, 2021)
The analysis of various forms of protest activity in the virtual space becomes especially relevant in the era of digital technologies development in all spheres of public life. But until now, there has not been a comprehensive work devoted to the trends that cause, accompany and organize digital protest activity in the world. The purpose of this paper is to determine the theoretical and methodological foundations of the socio-political analysis of digital protest activity in modern societies. The study solved the problems of analyzing the values of provincial Russian societies, institutional matrices, network political management and specific forms of virtual communication in the network space. The authors reveal the theoretical and methodological foundations of the development of digital protest activity in the world: features of social temporality, public values, specifics of trust, types of social connections in urban space; digitalization, virtualization and mediativization, information inequality, digital elitism; institutional matrices and institutional traps of electronic communication, trends in digital management. The theoretical grounds provided are the basis of digital simulation of the protest activity in Megacities and provincial towns.